(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Graphene, a monolayer of carbon atoms packed in a hexagonal structure, has become one of the most remarkable materials available to condensed matter physics and material science(engineering) today due to its nobel structural and electronic properties. In this paper, the structural, electronic, and magnetic properties of Mn-doped monolayer pristine graphene is studied using spin-polarized density functional theory (DFT). The results show that the substitution of Mn dopant atom at the C sites is energetically favorable and the dopants are strongly hybridized with neighboring C-atoms of graphene. The total density of state (TDOS), partial density of state (PDOS), and energy band structure calculations results revel that the electronic and magnetic properties of pristine graphene is being affected in the presence of Mn dopants. Thus, in the presence of Mn dopants nonmagnetic(paramagnetic) and metallic state of pristine graphene is turned to half-metallic with the ferromagnetic ground state. Based on result, we recommend that Mn doped graphene is Nobel material for spintronics and magnetic information storage applications.